A novel metamaterial gain-waveguide nanolaser. (October 2021) - Awad, Ehab
Graphical abstract: Highlights: A novel nano-laser is demonstrated. It is built around a new nano metamaterial gain waveguide. The metamaterial can efficiently enhance both pump power absorption and lasing efficiency. The nano-laser shows a very small optical threshold and high quantum efficiency. It has a compact size and can be promising for on-chip optical communications. Abstract: Researchers in silicon photonics have been searching for suitable and efficient light-emitting sources that are compatible with silicon-on-insulator technology. In this work, a novel continuous-wave silicon compatible metamaterial nanolaser was designed and numerically demonstrated. This novel nanolaser was constructed around a new metamaterial traveling-wave gain-waveguide, which was placed in line with silicon-on-insulator input and output waveguides, and lases at 1550 nm (i.e., in the telecom range) when pumped at 800 nm. The metamaterial waveguide consists of periodic and alternating nanoscale gain stripes (InGaAsP) and air gaps. It supports fundamental single-mode propagation for both pump and laser signals. It can efficiently couple light into the input and output silicon waveguides. The laser gives simultaneous forward and backward outputs. Besides, the metamaterial allows for efficient pump-power absorption and laser emission, which results in an almost ideal internal quantum efficiency (≅99.1%), low lasing threshold (≅200 µW), very good lasing slope efficiency (≅43.5%), and narrow laser linewidth (≅0.88 nm).